2021
DOI: 10.1002/aqc.3700
|View full text |Cite
|
Sign up to set email alerts
|

Use of diet and body condition assessments as intermediate indicators of translocation success in the Critically Endangered Philippine crocodile (Crocodylus mindorensis)

Abstract: Intermediate metrics of translocation success are useful for long‐lived, slow to mature species where survival and reproduction happen over decades. With fewer than 150 individuals in the wild, the Critically Endangered Philippine crocodile (Crocodylus mindorensis) is one of the most threatened species on Earth. This study presents the first analysis of diet and body condition of wild Philippine crocodiles and headstarted (i.e. captive‐reared) individuals released into the wild over the last decade, and uses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…(2006) found that 32.1% of juvenile falcons ( Falco peregrinus ) dispersed prematurely and Brown et al. (2021) found up to 92.7% of subadult crocodiles ( Crocodylus mindorensis ) released could not be recaptured in the study area.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…(2006) found that 32.1% of juvenile falcons ( Falco peregrinus ) dispersed prematurely and Brown et al. (2021) found up to 92.7% of subadult crocodiles ( Crocodylus mindorensis ) released could not be recaptured in the study area.…”
Section: Resultsmentioning
confidence: 84%
“…All returned to their source location within 1 month (Read et al., 2007). When releasing subadult crocodiles ( Crocodylus mindorensis ), up to 92.7% released were unable to be recaptured from the study area, likely due to a combination of hyperdispersal, mortality, and trap avoidance following release (Brown et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the scale of ONE, and the behavioural, morphological and evolutionary consequences on inappropriate captive rearing protocols (Alberts 2007; Passos et al 2017; Brown et al 2021) the natural kiwi chick diets, and their region-specific nutritional needs should become a research priority. It is known that when species are nutritionally mis-matched to their optimal, dynamic, natural diet, individuals can over- or under-investment in life history traits, especially those associated directly with adult fitness (Lee et al 2008; Solon-Biet et al 2015; Gray et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of dietary requirements is important for translocation planning and monitoring. For example, an understanding of diet was important for assessing the post-release dietary similarity of translocated versus resident crocodilians as a measure of translocation success in the critically endangered Philippine crocodile (Crocodylus mindorensis [120]). This was a useful alternative to fecundity as an assessment measure due to the long lifespan of the species that would require decades of monitoring data using conventional analysis of reproductive success [120].…”
Section: Looking Forwardmentioning
confidence: 99%